MicroRNA-34a activation in tuberous sclerosis complex during early brain development may lead to impaired corticogenesis - Korotkov, Anatoly; Sim, Nam Suk; Luinenburg, Mark J; Anink, Jasper J; van Scheppingen, Jackelien; Zimmer, Till S; Bongaarts, Anika; Broekaart, Diede W M; Mijnsbergen, Caroline; Jansen, Floor E; Van Hecke, Wim; Spliet, Wim G M; et al. (Neuropathology and applied neurobiology, 2021)
AIMS: Tuberous sclerosis complex (TSC) is a genetic disorder associated with dysregulation of the mechanistic target of rapamycin complex 1 (mTORC1) signalling pathway. Neurodevelopmental disorders, frequently present in TSC, are linked to cortical tubers in the brain. We previously reported microRNA-34a (miR-34a) among the most upregulated miRs in tubers. Here, we characterised miR-34a expression in tubers with the focus on the early brain development and assessed the regulation of mTORC1 pathway and corticogenesis by miR-34a. METHODS: We analysed the expression of miR-34a in resected cortical tubers (n = 37) compared with autopsy-derived control tissue (n = 27). The effect of miR-34a overexpression on corticogenesis was assessed in mice at E18. The regulation of the mTORC1 pathway and the expression of the bioinformatically predicted target genes were assessed in primary astrocyte cultures from three patients with TSC and in SH-SY5Y cells following miR-34a transfection. RESULTS: The peak of miR-34a overexpression in tubers was observed during infancy, concomitant with the presence of pathological markers, particularly in giant cells and dysmorphic neurons. miR-34a was also strongly expressed in foetal TSC cortex. Overexpression of miR-34a in mouse embryos decreased the percentage of cells migrated to the cortical plate. The transfection of miR-34a mimic in TSC astrocytes negatively regulated mTORC1 and decreased the expression of the target genes RAS related (RRAS) and NOTCH1. CONCLUSIONS: MicroRNA-34a is most highly overexpressed in tubers during foetal and early postnatal brain development. miR-34a can negatively regulate mTORC1; however, it may also contribute to abnormal corticogenesis in TSC.
Keywords: dospělí; Animals; Female; astrocyty; Infant; dítě; předškolní dítě; Adult; ženské pohlaví; mladý dospělý; Adolescent; lidé; neurony; signální transdukce; mozek; Signal Transduction; Astrocytes; Neurons; Tuberous Sclerosis; Male; kojenec; Brain; Child, Preschool; Young Adult; mikro RNA; tuberózní skleróza; mozková kůra; Cerebral Cortex; Child; MicroRNAs; zvířata; mužské pohlaví; Mice, Inbred C57BL; mladiství; myši inbrední C57BL; Humans